O14 Using point of care simulation to detect latent hazards of a massive haemorrhage protocol. (November 2018) - Nadarajah, Premala; Li, Anna; Benham-Hermetz, Julia; Emanuel-Kole, Lola
Abstract : In order to assess the reliability of the MHP a series of high fidelity simulations were carried out across the trust between 08/2017–05/2018. The aim was to identify any latent hazards and potential failure modes along the MHP pathway. Methods: We delivered high fidelity point of care simulations in clinical areas. The multidisciplinary teams involved all the relevant clinical teams who would routinely be involved in a MHP activation. These included switchboard services, blood transfusion laboratory, clinical haematology, crash teams, and the clinical team in their clinical areas. The simulations were run for 20–30 min as an end-to end scenario where blood units were collected in real time. This was followed by structured debriefing by two trained simulation debriefers. The pathway was also independently evaluated by another observer using a simplified failure modes and effects analysis (FMEA). This ensured that hazards not recognised by debriefers or participants were also captured. Participating teams were asked for written feedback regarding the simulation training and any further safety issues. Results: Latent Hazards and Failure Modes identified were: Delays in recognition & activation of MHP. Lack of awareness of the MHP and locating the protocol. Communication failures between clinical staff and blood transfusion laboratory. Failure of team to assign leadership & team roles. Teams were unaware of nearest source of O negative blood. Blood samples not taken in a timely fashion leading to delays in processing in laboratory. Fibrinogen levels not being ordered. Tranexamic acid not being stocked on all wards. Actions taken: A Major Haemorrhage Box was designed to aid timely delivery of care. Contents: Simplified MHP for wards and remote area use. Clear signposting of nearest blood fridge Simplified action cards with roles and clear leadership tasks Blood sample bottles and prefilled request forms Tranexamic acid and instructions on administration. Conclusion: Human reliability analysis methods are routinely used in high risk industries such as nuclear and gas industries to identify and assess possible failure modes in any new design. Its use in healthcare is limited. This project attempts to use a simplified failure modes analysis to provide a structured way to assess how factors such as communication, workload, ergonomic design and decision making affect the major haemorrhage pathway. Anticipating patient safety issues in the design stage will reduce the risks to both patients and clinicians using the MHP. References: Vincent C, Burnett S, Cathey J. The measurement and monitoring of safety 2013. London: The Health Foundation: 13–30. Ventre KM, Barry JS, Davis D, et al. Using in situ simulation to evaluate operational readiness of a children's hospital-based obstetrics unit. Simulation in Healthcare2014;9(2):9–11.